2015
DOI: 10.1016/j.amjsurg.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in adults and the role of evolving computed tomography technology

Abstract: BACKGROUND The purpose of this study was to describe a single institution’s experience with adult intussusception and determine how this was influenced by evolving computed tomography (CT) technology. METHODS Adults treated between 1978 and 2013 for intussusception were reviewed. CT utilization and utilization of multislice technology over time were determined. Sensitivity of CT was calculated. RESULTS A total of 318 patients were identified. CT utilization was 72% and it increased over time. The number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 10 publications
(13 reference statements)
4
38
0
3
Order By: Relevance
“…Interestingly, more recent studies have shown a pathologic lead point has become increasingly less common in adult intussusception [1,3,9]. Amr et al [1] have attributed this increase in identification of idiopathic cases partly due to widespread use of CT scans enabling the diagnosis of intussusception in patients without a lead point.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, more recent studies have shown a pathologic lead point has become increasingly less common in adult intussusception [1,3,9]. Amr et al [1] have attributed this increase in identification of idiopathic cases partly due to widespread use of CT scans enabling the diagnosis of intussusception in patients without a lead point.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, adult intussusception is much less common in comparison to the incidence of pediatric cases, only accounting for 5% of all intussusceptions [5,6]. Due to its rarity, there are no large-scale studies or meta-analyses published to define appropriate guidelines for optimal management of adult intussusception [1,7]. Secondly, adult intussusceptions are often secondary to presence of a lead point, including malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations